The chemical profiling of loquat leaf extract by HPLC-DAD-ESI-MS and its effects on hyperlipidemia and hyperglycemia in rats induced by a high-fat and fructose diet. Issue 2 (26th January 2017) - Chen, Bo; Long, Piaopiao; Sun, Yue; Meng, Qilu; Liu, Xingxun; Cui, Huanhuan; Lv, Qingya; Zhang, Liang
Abstract : The inhibitory effects of loquat leaf extract (LLE) on pancreatic α-amylase, α-glucosidase and hyperlipidemia were evaluated. Abstract : In this study, the inhibitory effects of loquat leaf extract (LLE) on pancreatic α-amylase and α-glucosidase, and the preventative effects of LLE on hyperlipidemia and hyperglycemia in rats induced by a high fat and fructose diet have been evaluated. The LLE was chemically described using a high performance liquid chromatography-diode array detector coupled with a mass spectrometer (HPLC-DAD-MS/MS). 20 compounds including phenolic acids, flavonoids and triterpene acids were tentatively identified with authentic compounds or by referring to published articles and accessible databases ( e.g. MassBank, METLIN). Enzyme activity measurements showed that the IC50 values of the LLE on α-amylase and α-glucosidase were 11.34 ± 1.04 mg mL −1 and 50.77 ± 1.04 μg mL −1, respectively. The calculated Michaelis–Menten constants indicated that the LLE is an effective inhibitor against α-glucosidase in a mixed-model competitive mode. The fluorescence data revealed that the LLE binds with α-amylase and α-glucosidase. The animal experiment results indicated that the LLE significantly decreased the levels of fasting blood glucose, and hepatic and serum triglycerides.